Segmentasi Pemakaian Listrik Menggunakan Fuzzy C-Means (Studi Kasus Unit PLTD Kota Lolo) - EFVY ZAMIDRA ZAM; HAIRUL CANDRA (DEPATI PARBO PRESS, 2018)
ABSTRACT Clustering is the process of grouping data into clusters based on certain parameters so that the objects within a cluster have a high degree of similarity to one another and very similar to other objects in the different clusters. Fuzzy C-Means is included in one of the clustering technique. In this paper Fuzzy C-Means technique is used to segment the amount of electrical energy consumption at certain hours on the same day. The results of this study were obtained after 15 iterations. And obtained two cluster centers. For cluster 1 consists of 5 members, and cluster 2 consists of 1 member. Keywords : Cluster, Fuzzy C-Means, Electric, Segmentation